Consider new dynamics in student‐athletes' marijuana use. Issue 5 (10th August 2022) - Neal, Timothy
Abstract : Between the NCAA modifying its THC‐testing policies and more states legalizing the recreational use of marijuana, intercollegiate athletics administrators are struggling to make appropriate adjustments in their departmental drug‐testing policies. Additionally, there's a growing advocacy to use marijuana as an adjunct mode of care for student‐athletes' physical and mental conditions. All of these changes leave college athletics administrators, risk managers, and general counsel offices with much to consider as they work to adapt to the ever‐evolving issue of marijuana use in intercollegiate athletics.